SOUTH AFRICA’S NUCLEAR DIPLOMACY SINCE THE TERMINATION OF ITS NUCLEAR WEAPONS PROGRAMME - Van Wyk, Jo-Ansie (Scientia Militaria - South African Journal of Military Studies, 2014)
This article reports on an analysis of South Africa’s nuclear diplomacy since the country terminated its nuclear weapons programme, and explains why it has not retracted on this position. Through the skilful use of strategies typically used by middle powers in their conduct of nuclear diplomacy as niche diplomacy, South Africa has succeeded in norm construction, identity formation, and securing a niche role for itself, which resulted in material and non-material advantages for post-apartheid and post-nuclear weapons South Africa.